Analisis Anggaran Investasi Dalam Pengambilan Keputusan Investasi - Siti Nur Reskiyawati Said (INDO PUBLISHING, 2026)
Investment budgeting is an essential component of corporate financial planning that serves as the basis for long-term investment decision-making. This study aims to analyze the role of investment budgeting, types of investment, investment feasibility assessment methods, sources of investment financing, and the relationship between risk and return in investment decisions. This research employed a descriptive qualitative approach using literature review and a case study of PT. Kharisma Abadi Arta Guna Luwuk. The research data were obtained from relevant scientific literature and company data analyzed using capital budgeting methods, namely Net Present Value (NPV), Payback Period (PP), Profitability Index (PI), and Accounting Rate of Return (ARR). The results indicate that investment budgeting plays a strategic role in helping companies allocate resources effectively, select profitable investment alternatives, and minimize decision-making risks. Furthermore, investment financing sources and the relationship between risk and return are important factors that should be considered in determining investment feasibility. The case study findings reveal that the stone cruiser machine replacement investment at PT. Kharisma Abadi Arta Guna Luwuk is feasible, with an NPV of IDR 4,480,418,187.754, a Payback Period of 1.9 years, a Profitability Index of 8.5, and an Accounting Rate of Return of 10.368%. These findings demonstrate that the application of capital budgeting methods can support more objective, effective, and value-oriented investment decision-making.